Teachers' dialogue in a learner centered professional development initiative In a us urban high school - Leticia Alvarez Gutiérrez; Patricia D. Quijada Cerecer (Sociedad Iberoamericana de Pedagogía Social, 2014)
Using paradigms emerging from Learner Centered Professional Development (LCPD), dialogic education and Transformative Pedagogical Practices (TPPs), this research study examined pedagogies that ignited a revitalization of shared values as a community of learners, challenged assumptions about learning while invigorating professional identities and cultivating possibilities for transforming praxis of a group of female teachers and female administrators in an urban high school. The LCPD initiative engaged teachers (13) and administrators (3) in dialogue, self-examination, and reflection, while also chipping away dearth perceptions of Latina/o student as learners and nourish possibilities for their successes. The data for this study is part of a larger corpus of data exploring teacher professional development initiatives in a large urban city in the southwestern region of Texas. Narrative analysis was the methodological tool used to code and analyze the data. The authors highlight the pedagogies that served to renew teachers and administrators' sense of community, professional identities and modifications of teachers' attitudes and pedagogies regarding themselves and Latina/o students. Our research findings underscore the urgency of educational reform to include on-going LCPD in order to transform and encourage professional enrichment, teacher agency and revive pedagogies that support all students' academic and social successes.